Indonesia Leader Forum, post-truth and political interests in social media and television - Mariana Ulfah; Amadou Barry (International Journal of Communication and Society, 2019)
This paper aims to how Indonesian Leaders Forum (ILF) as a new talkshow program in Indonesia effort to increasing political interest of citizens. This research uses descriptive qualitative method with a case study of the ILF Program. By using descriptive method, the author can explain the background of the incident, some perspective on the event and analyze in depth. So the ILF can answer the public's concerns about the political situation in Indonesia today conclusion contains the main points of the article.